Bone marrow stem cells modified with human interleukin 10 attenuate acute rejection in rat lung allotransplantation. (25th July 2017) - Pieróg, Jarosław; Tamo, Luca; Fakin, Richard; Kocher, Gregor; Gugger, Mathias; Grodzki, Tomasz; Geiser, Thomas; Gazdhar, Amiq; Schmid, Ralph A
Abstract: OBJECTIVES: The aim of this study was to investigate new therapeutic options to attenuate acute rejection in a rat lung allograft model. Cell-based gene therapies have recently been reported as a novel curative option in acute and chronic diseases for which conventional treatments are not available. We studied the effect of human interleukin 10 (hIL-10) on expressing bone marrow-derived mesenchymal stem cells (BMSCs) in combination with cyclosporine A (CsA) on acute rejection of lung allografts in the rat. METHODS: Lung allotransplantation was performed from male Brown Norway donor to male Fisher (F344) rats. Rat BMSCs were transfected with hIL-10 in vitro and introduced in the graft prior to implantation. Group A ( n  = 5) received CsA intraperitoneally (2.5 mg/kg body weight) for 5 days post-transplant; Group B ( n  = 5) received BMSC and CsA and Group C ( n  = 5) received hIL-10-BMSC before implantation and CsA. Graft function was assessed by blood gas levels only from the graft on day 5; tissue was sampled for histological grading of rejection and measurement of the wet-to-dry ratio. RESULTS: All Group A control animals showed severe signs of rejection. On Day 5, all grafts in Group C showed improved gas exchange (mean arterial partial pressure of oxygen 222.2 ± 40.38 mmHg vs 92.36 ± 20.92 mmHg in Group B and 42.72 ± 18.07 mmHg in Group A). Histological examination revealed moderate-to-severe rejection in all animals in Group A [International Society for Heart and Lung Transplantation Level III B (ISHLT)] in contrast to low-to-moderate rejection in Group B (II–IIIA) and much improved histological grade in Group C (I–IIA). Moreover, the wet-to-dry ratio was also reduced in Group C (4.8 ± 1.19 compared with 4.78 ± 0.62 in Group B and 9.36 ± 0.90 in Group A). CONCLUSIONS: The hIL-10 BMSC represent a promising novel method for localized cell-based gene therapy for acute rejection in a rat lung allograft model.